2021
DOI: 10.1021/acsami.1c15959
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Supramolecular Adhesion to Wet and Soft Surfaces via Solvent Exchange

Abstract: A series of poly­(thioctic acid-catechol)­s was prepared by supramolecular copolymerization of two low-molecular-weight monomers, thioctic acid (TA) and catechol (CA). The addition of a small amount of CA molecules significantly improved the adhesion ability of poly­(TA) and transformed it into an applicable supramolecular polymer adhesive material. The robust adhesion of poly­(TA-CA)­s to soft surfaces was achieved by employing a hot-melt method. However, the supramolecular adhesion via the hot-melt method fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Generally, for solvent-exchange-induced adhesion, most of the gels are first attached to the substrates, and then they are immersed in water to yield an adhesive hydrogel layer by in situ solvent exchange. ,, For example, Zhao et al reported underwater contact adhesion in polyelectrolyte complexes actuated by water–DMSO solvent exchange, where the premixed polyanion and polycation DMSO solution was cast on the various substrates and the substrates were applied in the water to allow the solvent exchange. Gao and co-workers also attached the organogel on the substrates to allow in situ solvent exchange in water, achieving underwater adhesion .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, for solvent-exchange-induced adhesion, most of the gels are first attached to the substrates, and then they are immersed in water to yield an adhesive hydrogel layer by in situ solvent exchange. ,, For example, Zhao et al reported underwater contact adhesion in polyelectrolyte complexes actuated by water–DMSO solvent exchange, where the premixed polyanion and polycation DMSO solution was cast on the various substrates and the substrates were applied in the water to allow the solvent exchange. Gao and co-workers also attached the organogel on the substrates to allow in situ solvent exchange in water, achieving underwater adhesion .…”
Section: Resultsmentioning
confidence: 99%
“…Catechol or resorcinol structures are crucial for supramolecular copolymerization, which is consistent with our previously reported study. 43…”
Section: Resultsmentioning
confidence: 99%
“…Catechol or resorcinol structures are crucial for supramolecular copolymerization, which is consistent with our previously reported study. 43 In addition to the chemical structures of the TPEs, the TPE content plays a significant role in the formation of poly(TA-TPE) materials: a high TPE content accelerates the copolymerization process. As shown in Fig.…”
Section: Preparation and Characterizationmentioning
confidence: 99%
“…21,22 Benefiting from an inherent disulfide bond and a carboxyl group, TA is used to prepare functional polymers which have the presence of a dynamic disulfide bond and a molecular hydrogen bond, simultaneously. 23,24 The polymerization of TA can be initiated under ultraviolet light, high temperature, and appropriate concentration due to the intrinsic crosslinking unit of TA. [24][25][26] However, the as-prepared polyTA is unstable which can reconvert into TA due to the terminal diradicals.…”
Section: Introductionmentioning
confidence: 99%